Cystophora cristata - Russell A. Mittermeier; Don E. Wilson (Lynx Edicions, 2014)
10. Hooded Seal Cystophora cristata French: Phoque a capuchon / German: Klappmtitze / Spanish: Foca de casco Other common names: Bladdernose Seal, Crested Seal Taxonomy. Phoca cristata Erxleben, 1777, “Habitat in Groenlandia australiori et Newfoundland” (= S Greenland and Newfoundland). Three distinct breeding stocks of C. cristata are often recognized, but molecular and morphological analyses suggest a single panmictic population. Monotypic. Distribution. N Atlantic Ocean at high latitudes, from NE Canada (Davis Strait S to Gulf of Saint Lawrence) to Greenland, Iceland, Jan Mayen, and Svalbard; seasonally, distribution extended N into the Arctic Ocean and S into the North Sea in the NE Atlantic Ocean. Descriptive notes. Total length 250-270 cm (males) and 200-220 cm (females); weight c.300 kg (males) and ¢.200 kg (females). Newborns are c.100 cm in length and weigh c.25 kg. Male Hooded Seals are longer and heavier than females, and exceptionally large males can weigh 400 kg. Hooded Seals are relatively large phocids, with a gray to silver pelage covered by dark splotches and spots; front and rear flippers are generally darker. Nose of a male Hooded Sealis larger than that of a female and can be inflated, especially in the breeding season during threat displays with other males. It starts to develop during puberty when males are about four years old. There is also a reddish membrane septum that internally separates left and right nostrils; adult males can expanded and extruded it through one of the nostrils to form an external balloon—also part of threat displays during the breeding season. Habitat. Dispersed throughout deep water of the North Atlantic Ocean off eastern Canada and south-western and south-eastern Greenland. Hooded Seals sparsely aggregate on seasonal pack ice in the North Atlantic Ocean to breed in late winter and early spring and to molt in spring and early summer. Food and Feeding. Diets of Hooded Seals are poorly known because they are pelagic for most of the year. Some prey includes Greenland ...